From Christ to Compassion: The Changing Language of Pastoral Care - Bernau, John A. (Journal for the scientific study of religion, 2021)
The rise of neurology, psychology, and psychiatry over the last 100 years has challenged the clergy's historical monopoly on dealing with “personal problems” and mental well-being. In this study, I document the changing language of pastoral care by analyzing over seventy years of academic articles in the Journal of Pastoral Care and Counseling (N = 4,054) using structural topic modeling. Ultimately, I reveal a linguistic shift from the universal to the particular as pastoral care professionals drop language of human nature and morality for that of individual narratives. I also find a decline of overtly religious language since the 1950s in favor of a more ecumenical language of spirituality, hope, and presence. Both of these trends take place alongside a push for “evidence-based” pastoral care. Together, these linguistic shifts offer insight into a seventy-year struggle to provide authentic religious care in a world of competing alternatives.